Proceedings of the international workshop on intergrated soil management for sustainable use of salt affected soils. (FAO, 1995)
The soil salinity model is intended as a practical model for the evaluation of salinity and sodicity problems. It includes the major ion chemical processess of cation exchange and solid phase dissolution and precipitation, water and solute movement under variably saturated conditions, plant growth and plant water uptake including the response to adverse environmental conditions such as salinity water stress and temperature.